ON THE GENETIC FECUNDITY AND RESILIENCE OF THE FEMALE SEX - Husainova , Xusniobod J (Innovative Development in Educational Activities, 2024)
The genetic resistance of females of natural animal species to adverse environmental factors seems to reduce the likelihood of the emergence of new traits through females and ensures the stability of the species.